Applicability of strain energy density criterion for fracture prediction of notched PLA specimens produced via fused deposition modeling. (December 2021) - Seibert, P.; Susmel, L.; Berto, F.; Kästner, M.; Razavi, S.M.J.
Highlights: Fracture behavior of 3D printed PLA specimens with various notch geometries is evaluated. Two different methods based on strain energy density are used for fracture prediction. Using an analogous approach showed significantly smaller scatter in fracture predictions. The accuracy of the failure predictions using SED and TCD is presented and discussed. Abstract: The Averaged Strain Energy Density (ASED) criterion is validated for the failure prediction of notched Polylactide Acid specimens fabricated by Fused Deposition Modeling by means of experimental data and the results are compared to the Theory of Critical Distances. The common approach of estimating the ASED control volume radius based on the measured fracture toughness was shown to be suboptimal, arguably because of the difficulties of obtaining the fracture toughness with such complex materials. Therefore, a more robust approach is evaluated in analogy of the TCD and it is shown to successfully extend the range of applicability of the ASED criterion.